2018
DOI: 10.1007/s41810-018-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter-comparison of Chemical Composition and Originality of Atmospheric PM10 at Coastal Regions and Offshore Islands in the Subtropical East Asia

Abstract: Inter-comparison on the chemical characteristics, spatiotemporal variation, and source originality of atmosphere PM 10 at the coastal regions and offshore islands of subtropical region in East Asia was investigated. A total of six sampling sites including three coastal and three island sites over the Minjiang estuary were selected for simultaneously manually sampling PM 10 to investigate the differences of coastal and island PM 10 concentration, chemical properties, and emission sources. After sampling, an ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Previous atmospheric PM 10 concentration measured at the Matsu Islands showed that PM 10 concentration in summer was always the lowest in the whole year, while high PM 10 concentrations were generally observed during the periods from late fall to early spring of the sequential year (Liao et al 2018 ). The temporal variation of PM 10 concentration correlated with wind direction in the marine boundary layer which was closely related with poor ambient air quality (Pollutants Standard Index, PSI > 100) during the prevalence of northeastern monsoons commonly occurs in the seasons of winter and spring.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous atmospheric PM 10 concentration measured at the Matsu Islands showed that PM 10 concentration in summer was always the lowest in the whole year, while high PM 10 concentrations were generally observed during the periods from late fall to early spring of the sequential year (Liao et al 2018 ). The temporal variation of PM 10 concentration correlated with wind direction in the marine boundary layer which was closely related with poor ambient air quality (Pollutants Standard Index, PSI > 100) during the prevalence of northeastern monsoons commonly occurs in the seasons of winter and spring.…”
Section: Introductionmentioning
confidence: 94%
“…Major stationary sources at the Matsu Islands include a 14.2-MW diesel-fired utility power plant, two breweries, and a few gas stations. However, high PM 10 concentration up to 129 μg/m 3 has been recorded by Taiwan EPA’s ambient air quality monitoring station located at the Nankang Island in the spring of 2011 (Liao et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%